2011
DOI: 10.2215/cjn.06190611
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pretransplant Serum Phosphorus with Posttransplant Outcomes

Abstract: SummaryBackground and objectives Serum phosphorus levels are associated with mortality, cardiovascular disease, and renal function loss in individuals with and without chronic kidney disease. The association of pretransplant serum phosphorus levels with transplant outcomes is not clear. The selected 9384 primary kidney recipients were divided into five groups according to pretransplant serum phosphorus levels (mg/dl): Ͻ3.5, 3.5 to Ͻ5.5 (reference group), 5.5 to Ͻ7.5, 7.5 to Ͻ9.5, and Ն9.5. Unadjusted and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
1
17
2
Order By: Relevance
“…Several studies have shown associations between serum phosphorus levels and decline in renal function in pediatric and adult patients with CKD (8-10), and graft failure in adult renal transplant patients (11,(13)(14)(15). Serum phosphorus levels above recommended targets were associated with a higher risk of graft loss, even after adjustment for eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown associations between serum phosphorus levels and decline in renal function in pediatric and adult patients with CKD (8-10), and graft failure in adult renal transplant patients (11,(13)(14)(15). Serum phosphorus levels above recommended targets were associated with a higher risk of graft loss, even after adjustment for eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in children (8) and adult patients with early (9) or advanced CKD (10), serum phosphorus was independently associated with a decline in renal function. Moreover, donor (11), pretransplant (12,13), and post-transplant (14-16) mineral levels have been associated with graft failure in adult renal graft recipients. Information on mineral metabolism in pediatric graft recipients mainly originates from small single-center studies with relatively short follow-up time (5,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The creation of the cohort has been described previously [28,29,30,31,32,33,34,35]. To minimize measurement variability, all repeated measures for each patient during any given calendar quarter, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with a pretransplant serum PTH level of 100 pg/ml, pretransplant PTH levels of 300 pg/ml, 500 pg/ml, and 800 pg/ ml were associated with approximately 20%, 40%, and 80% higher risk of graft failure censored death, respectively (13). Similarly to PTH, pretransplant (12) and post-transplant (15) serum phosphorous levels were associated with increased mortality risk in kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 95%
“…However, only few studies aimed to analyze the association between pretransplant MBDs and post-transplant outcome. We recently examined only the association of pretransplant phosphorus level and post-transplant outcome (12). However, similar investigations for other routinely measured MBD measures, such as alkaline phosphatase, intact parathyroid hormone (iPTH), and calcium, have not yet been examined in a large cohort.…”
Section: Introductionmentioning
confidence: 99%